Program Sadaya Langgar: Meningkatkan Keterampilan Budidaya Kelor dan Kawista untuk Ketahanan Pangan di Desa Langgar, Rembang - Akmal Maulana, Muhammad; Septiawati, Indah Zahra; Putri, Cindy Yuliani; Zulmi, Fathiah Zahrani; Salamah, Eneng Lulu; Kurniawan, Muhammad Fabio Rayhan; Yuwendri, Dhanny Fadillah Rafiuh Drajad; Elysia, Laili; Widjaja, Hermanu (Jurnal Pusat Inovasi Masyarakat, 2025)
The Sadaya Langgar program aims to enhance the knowledge and skills of the community in propagating and cultivating moringa and kawista plants, while also improving village food security and optimizing land use. The program targets the Women's Farming Group (KWT) and the broader community of Langgar Village. Its implementation consists of three stages: socialization, demonstration, and monitoring. Activities include techniques for propagation, planting, and the utilization of plant products. The program has successfully increased the community's understanding of the importance of moringa as a high-nutrient food source and kawista as an herbal remedy. As a result, the community, particularly KWT members, has shown improvements in cultivation skills and the utilization of these plants, positively impacting food security and the village's economic well-being. The Sadaya Langgar program not only enhances technical skills in cultivation but also contributes to overall community health through educational activities about the nutritional content of moringa.